The Influence of the Marketing Mix on Buccheri Products at the Buccheri Store in Medan Mall - Khaira Rizfia Fahrudin (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This research was conducted at the Buccheri store located in Medan Mall, Jalan M.T. Haryono No. 8. The study was carried out from November 2025 to January 2026. The types of data used in this research consisted of primary and secondary data, with a total sample of 100 respondents. The sampling technique used was the Slovin method. To analyze variable X, the researcher distributed questionnaires to Buccheri product consumers using the accidental sampling method, conducted interviews with Buccheri management, and utilized SPSS software to test the validity and reliability of the questions and answers in this study. Based on the research results, it was found that the statements receiving “agree” and “strongly agree” responses regarding product, price, promotion, and place were positively evaluated by consumers. This is evidenced by the average response rate for product at 77.0%. The average response for price was 74.0%. For promotion, the average “agree” and “strongly agree” responses amounted to 71.0%, and for place, 74.0%. From the analysis conducted, it can be concluded that the management of Buccheri has implemented the marketing mix concept effectively, as reflected in the significant and high level of agreement among respondents. Therefore, although the results are positive, Buccheri should continue to maintain and further improve its product, price, promotion, and place strategies, especially by optimizing any indicators that are not yet fully maximized, in order to achieve the company’s vision and mission and ensure sustainable growth in the future.